Autonomy, Incentives, and School Performance: Evidence from the 2009 Autonomous Private High School Policy in Korea - Yoon Soo Park (KDI Journal of Economic Policy, 2016)
Improving the quality of school education is one of the key policy concerns in Korea. This paper examines whether providing schools with adequate autonomy and incentives can meet the policy goals by looking at a recent policy reform in Korea. In 2009, the Korean government granted autonomy to certain private high schools on the condition that no financial subsidies would be provided to the schools. Because the autonomous private high schools cannot receive a subsidy, they have a strong incentive to meet parental demands because schools failing to meet these demands will lose students and will have to close. Applying the value-added model to longitudinal data at the student level, I find that students entering these autonomous schools show faster growth in their academic achievement than their peers in traditional non-autonomous schools. These results suggest that providing schools with autonomy and incentives can be a useful policy tool for improving school education.
Keywords: I20; I28; C21; 330; Autonomous Private High School; School Effect; Academic Achievement; School Autonomy; Secondary Education in Korea